PENGARUH PENGGUNAAN MEDIA QUIZWHIZZER TERHADAP HASIL BELAJAR SISWA PADA MATERI IPAS KELAS V UPTD SD NEGERI BATUPLAT 1 - tafuli, Novianty kory; koro, Maxsel; Adoe, Treesly y. N. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Elementary School subjects that combine Natural Sciences (IPA) and Social Sciences (IPS) are Natural and Social Sciences (IPAS). This subject studies living things, inanimate objects, and the interactions between the two, as well as human life as individuals and social beings who interact with their environment. Therefore, supporting tools are needed in the learning process that occurs in the classroom such as innovative learning media to facilitate student understanding. Learning media are tools or means used in the teaching and learning process to facilitate the delivery of material and increase the effectiveness of learning, for example quizwhizzer, an interactive game-based learning platform designed to make the learning process more interesting and enjoyable. Based on the study above, this study focuses on testing this application as a learning medium in the material of sounds around us for fifth grade students at Batuplat 1 Elementary School using a quantitative approach.